QTL and candidate gene analyses of rootstock-mediated mandarin fruit yield and quality traits under contrasting iron availabilities - Asins, María J.; Raga, Verónica; Roca, Dolors; Carbonell, Emilio A. (Springer, 2020)
The most sustainable approach to overcome iron deficiency in fruit crops is breeding for rootstocks with a higher capability to acquire iron (Fe) from the soil. The objective of this study was quantitative trait loci (QTL) and candidate gene analyses of rootstock-mediated low-Fe tolerance in terms of fruit yield and quality traits, including Fe fruit content, in a satsuma mandaringrafted rootstock population derived from a cross between Citrus reshni (Cleopatra mandarin) and Poncirus trifoliata, under sufficient and low-Fe fertilization (15.3 vs 5.2 μM Fe, respectively). Iron reduction to one-third significantly decreased satsuma leaf chlorophyll concentration, fruit iron concentration, and the fruit/leaf iron proportion. Thirty-four QTLs were detected for 46 heritable traits. Eighteen of them were also found significant when testing each parental genome separately. Seven QTLs contributed to the fruit concentrations of Cu, Fe, K, Na, and S. QTLs involved in rootstock mediated tolerance to Fe deficiency and fruit quality traits distributed into five genomic regions whose gene contents (assuming collinearity with the C. clementina genome) were investigated for overrepresented molecular functions and biological processes, and putative functional candidates. Among them, a metal-NA-transporter YSL3 (Ciclev 10019170m), four phytochelatin synthases, an iron-chelate-transporter ATPase, and four basic/helix-loop helix genes coding for likely relevant transcription factors in Fe homeostasis under Fe deficiency were found as follows: bHLH3 (Ciclev10019816m), bHLH137.1 (Ciclev10031873m), bHLH123 (Ciclev10008228m), and ILR3 (Ciclev10009354m). Genes within three QTL regions supported a genetic connection between rootstock-mediated tolerance to Fe deficiency and biotic stresses in citrus.